2008
DOI: 10.1097/ijg.0b013e3181629a02
|View full text |Cite
|
Sign up to set email alerts
|

Blood Vessel Contributions to Retinal Nerve Fiber Layer Thickness Profiles Measured With Optical Coherence Tomography

Abstract: Purpose-To understand better the influence of retinal blood vessels (BVs) on the interindividual variation in the retinal nerve fiber layer (RNFL) thickness measured with optical coherence tomography (OCT).Subjects and Methods-RNFL thickness profiles were measured by OCT in 16 control individuals and 16 patients. The patients had advanced glaucoma defined by abnormal disc appearance, abnormal visual fields, and a mean visual field deviation worse than − 10 dB.Results-In general, the OCT RNFL thickness profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
165
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(189 citation statements)
references
References 24 publications
19
165
2
3
Order By: Relevance
“…This discrepancy between studies may be due to the difference in patient populations, devices for RNFL measurements, or study designs. It has been suggested that the peripapillary RNFL thickness profiles measured with OCT vary among individuals, and this variation was large relative to other factors, such as measurement error [25,26], optic disc size [27], or the retinal arterioles and venules extending from the optic disc [28].…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy between studies may be due to the difference in patient populations, devices for RNFL measurements, or study designs. It has been suggested that the peripapillary RNFL thickness profiles measured with OCT vary among individuals, and this variation was large relative to other factors, such as measurement error [25,26], optic disc size [27], or the retinal arterioles and venules extending from the optic disc [28].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the rate of optic disc, RNFL, and visual field decline is characterized by considerable variability both within and between individuals. 26,[28][29][30][31][32][33] To our knowledge, this is the first study to demonstrate progressive macular thickness atrophy in eyes with SAP progression. Our results differ from those published by Medeiros et al, 23 in which no detectable macular thickness loss over time was detected among 31 of 253 (13%) eyes that demonstrated progressive changes by stereophotographs and/or SAP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that children with low birth weight have narrower arterioles, 19 and arteriolar caliber is positively correlated with RNFL thickness and macular thickness. [20][21][22] Therefore, narrower vessels in preterm children compared with normal full-term controls could induce artifactually thinned RNFL measured by OCT. 23 Further histologic studies could help to clarify this idea.…”
Section: Variablementioning
confidence: 99%